The Islamic root of sympathy based morality: a case study of Adam Smith, Darwin and their relation with the teachings of the Prophet Muhammad (peace be upon him) - Ali, Muhammad Mumtaz; Siddiqui, Naseeb Ahmed (Institute of Social Sciences & Development, 2022)
What brings morality into existence found extensive interpretation since ancient times and one is more persuading than the other. However, following the enlightenment’s empirical approach to which Darwin and Adam Smith turned their attention for every moral dilemma lies in the concept of Sympathy. Both the authors believe, though without logical proof but based on the observation that it is the innate consciousness of Sympathy towards fellow beings responsible for the judgment on morality. Adam smith combined the struggle and sentiments as the sole premise to judge an ethical approach in society. Darwin with his concept of the evolution struggled to explain that sympathy in human lineage evolved into social instincts that gave it a more general flavor, strict empiricism. The question this article formulates is that was the concept of morality based on sympathy was a new and Western concept? Therefore, at first this article will detail the concepts of sympathy understood by Adam Smith and Darwin. It will highlight the process and situation behind such approach contextualizing the role of evolution. In the second part this article will discuss this concept of sympathy based morality in the teachings of the Prophet of Islam (peace be upon him) where he not only understood the nature of human existence but also evolved a new Medinan society. Moreover, it shows the contrasts and similarities between Islamic and Western understanding of sympathy based morality. Hence, it opens a new window to look at intellectual heritage and their relations.